PELATIHAN DAN PENDAMPINGAN PEMBUATAN MOCHI BERBAHAN BAKU BEKATUL DI DESA BEKUT - Syahrulizar Arditiya; Abdul Karim; Crisna Aprilia; Dian Hardiyanti; Erdiana Laura; Hesty Sulistiya; Khofifah Khofifah; Muniza Muniza; Kiki Kristiandi (STAI Darul Qalam Tangerang, 2022)
Bekut Village is located in the Tebas District area of West Kalimantan Sambas Regency. The village has its livelihoods: farmers, self-employed, civil servants, and other occupations. The most processed side products in Bekut Village are rice bran. The activity took place in March 2022, with the number of participants participating at 21 participants. This activity aims to provide training and assistance in making mochi made from rice bran in Bekut Village, Tebas District, Sambas Regency. The approach carried out by this training has several stages. The first is the presentation of materials, the second is the process of making bran mochi, the third is a discussion of training activities, and the fourth is evaluation. The results of the live interview conducted showed that PKK mothers have never processed rice bran; besides that, rice bran is not utilized effectively. After this activity, the movement has benefits where the byproducts of rice can be used as products with high economic value and valuable nutrients. In addition, this training is efficient; enthusiastic participants are also interested in contributing directly to this training process